Digital Marketing Communication In Building The Image Of Local Cuisine Products @ter.dimsum.dimsum - Dema Guhaningtias; Siti Khumayah; Aghnia Dian Lestari (Jurnal Ekuisci, 2026)
Background. The development of digital technology has encouraged MSMEs to utilize social media as a primary marketing tool, particularly Instagram, which is visual and interactive. Aims. This study aims to analyze the digital marketing communication strategies on the Instagram account @ter.dimsum.dimsum in building the image of local culinary products. Methods. The method used is descriptive qualitative method, with data collection techniques of interviews with business owners, observation of Instagram content, and documentation. The data were analyzed through the stages of reduction, presentation, and drawing conclusions. Result. The results indicate that @ter.dimsum.dimsum primarily leverages visual content, simple narratives, and two-way interaction. From a digital marketing perspective, the "product" element is highlighted through appetizing food photos and videos; "price" is communicated transparently; "place" is realized through Instagram’s role as a digital space integrated with delivery services; and "promotion" is conducted organically via the feed, Stories, and Reels. Supporting factors include the product’s visual appeal, a communicative writing style, and responsiveness to consumers. Limiting factors include resource constraints, the absence of a structured posting schedule, limited content variety, and suboptimal follow-up promotion. Conclusion. This study concludes that digital marketing communication plays a significant role in building the image of local culinary products, but still requires strengthening in terms of planning and strategic consistency.